Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy and Artificial Neural Networks Applied to Differentiate Escherichia coli papG+/papG- Strains - Łukasz Lechowicz; Wioletta Adamus-Białek; Wiesław Kaca (Journal of Spectroscopy)
Fimbriae are an important pathogenic factor of Escherichia coli during development of urinary tract infections. Here, we describe a new method for identification of Escherichia coli papG+ from papG- strains using the attenuated total reflectance Fourier transform infrared Spectroscopy (ATR FT-IR). We applied artificial neural networks to the analysis of the ATR FT-IR results. These methods allowed to discriminate E. coli papG+ from papG- strains with accuracy of 99%.